Design and optimization strategy of HAWT using a local pitch angle adaptation - Meghlaoui, Issam; Layadi, Toufik Madani (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
In this paper, a smart design of a horizontal wind turbine (HAWT) has been developed. The developed design allows improving kinetic energy recuperation with high efficiency. The considered design of the wind turbine is characterized by a specific mechanical structure of blades. Each blade contains separated elements with an adaptable local pitch angle. To develop the smart wind turbine, a new algorithm for controlling the blade elements has been implemented. It allows estimating the distribution of the twist angle of each blade element. The achieved twist angle corresponds to the extracted optimal power provides by the wind turbine. The obtained results show a significant improvement relative to the wind turbine power coefficient under operating conditions. In fact, for some rotating velocity, the rate of this coefficient is increased by 21%. Moreover, notable kinetic energy recuperation is observed. Furthermore, smart orientation of elements proved optimal energy recuperation for a large scale of tip speed ratio and wind speed. In addition, the proposed structure of the wind turbine is more beneficial to minimize the axial thrust. Furthermore, the axial thrust of the wind turbine has been decreased by 21% for some operating velocity and specific conditions. As perspectives for the future works many ideas are suggested.